Squeezing, Then Stacking: From Breathing Pores to Three‐Dimensional Ionic Self‐Assembly under Electrochemical Control1. Issue 47 (24th September 2014) - Cui, Kang; Mali, Kunal S.; Ivasenko, Oleksandr; Wu, Dongqing; Feng, Xinliang; Walter, Michael; Müllen, Klaus; De Feyter, Steven; Mertens, Stijn F. L.
Abstract We demonstrate the spontaneous and reversible transition between the two‐ and three‐dimensional self‐assembly of a supramolecular system at the solid–liquid interface under electrochemical conditions, using in situ scanning tunneling microscopy. By tuning the interfacial potential, we can selectively organize our target molecules in an open porous pattern, fill these pores to form an auto‐host–guest structure, or stack the building blocks in a stratified bilayer. Using a simple electrostatic model, we rationalize which charge density is required to enable bilayer formation, and conversely, which molecular size/charge ratio is necessary in the design of new building blocks. Our results may lead to a new class of electrochemically controlled dynamic host–guest systems, artificial receptors, and smart materials.